PEMBANGUNAN EKONOMI DALAM PERSPEKTIF ISLAM - MOCH. CAHYO SUCIPTO MOCH. CAHYO SUCIPTO (POLITEKNIK PIKSI GANESHA, 2018)
This study intends to obtain a description of the principles, values, goals and differences between Islamic economics and other economics. The research method used is descriptive and qualitative methods. Data collection is carried out by the Archival Research method, which is collecting data that is generally in the form of evidence, notes, or historical reports that have been compiled in archives (documentary data) which are published and which are not published. The results of this study stated that Islamic economics combines individual benefits and general benefits to achieve balance and justice in society. Based on the above view, Islam stands on three fundamental pillars namely: 1) view of ownership (AI-Milkiyyah), ownership (property), 2) Management of Ownership (at-tasharruf fi al milkiyah), and 3) distribution of wealth in the middle amid humans.